De-Industrialization Patterns of Azerbaijan: Potential Outcomes of Dutch Disease Syndrome - Ibrahim Niftiyev (SSRN, 2018)
This paper focuses on the particular channels of de-industrialization processes of Azerbaijan considering the Dutch disease syndrome as the theoretical framework. After the emergence of the Dutch disease hypotheses, many resource-rich countries have been the main research object of it. One consequence of the Dutch disease syndrome is a shrinking manufacturing sector compared to the booming sector and the services sector. In order to shed light on this aspect of the Azerbaijan economy, important literature examples were examined and mainly descriptive statistics applied to visualize the economy's most recent timeline. This research mainly brings back the actuality of the Dutch disease phenomena to Azerbaijan's economy, depicting and comparing policy responses of the national government.
Keywords: P28; Q33; L60; 330; Azerbaijan economy; Dutch disease; de-industrialization; real effective exchange rate; sectoral output